ESG in Private Equity: How Have Private Equity Attitudes Concerning ESG evolved and Changed Over the Last Decade? - Embling, Nicholas (2020)
This research set out to systematically determine how attitudes within the private equity industry have evolved over the last decade as it pertains to environmental, social and corporate governance (ESG) factors, as ESG nowadays becomes increasingly more a part of corporate activity. Through interviews with various private equity personnel, the results returned that essentially the rise in prominence of ESG has had little to no impact on the attitudes of private equity investors regarding their primary mandate, that being return on investment. Their attitudes were very much primarily geared to maximising the wealth of their investors and not ESG principally. However, ESG as an afterthought once the fundamental goal of private equity has been considered has become far more imbedded within the attitudes and thought processes of the private equity industry. This has been highlighted by an evolving view of fiduciary duty within the industry to include ESG, as well as the development and progression of private equity ESG attitudes to meet increasing calls for greater ESG implementation from underlying investors. These notions have impacted upon the private equity industry in various ways, which has subsequently lead to increasing measures being implemented to profit from ESG within the industry. Although private equity ESG attitudes have progressed positively in this sense, the research found that attitudes regarding climate change had not, and that in fact these attitudes were somewhat indifferent and apathetic as a lack of consumer demand and other social issues begin to overtake climate as the major ESG talking point.